ARBITRASE NASIONAL DENGAN ARBITRASE SYARIAH: SUATU KAJIAN PERBANDINGAN - Fitriyanti, Fadia (Jurnal Media Hukum, 2013)
In the business world, of course, many considerations that underlie the business actors to choose arbitration as a dispute resolution efforts for dispute that will or they face. Among the advantages of arbitration over court based on Arbitration Act are the parties can choose the arbitrator. Although in the arbitration the parties can select arbitrators who are experts in their fields, seem the consideration to establish BASYARNAS (The National Sharia Arbitration Board) at first certainly raises the pros and cons. Based on the description of the background of  the above problems then the formulation of the problem is how the comparison between national arbitration and sharia arbitration where the discussion focused on Rules and Procedures of BANI  (The Indonesia  National  Board  of Arbitration) and BASYARNAS. The substance of  similarities between  National arbitration and Sharia arbitration in the same way of resolving disputes other than through the courts or alqadla. With regard to the legal basis for the enactment of a national arbitration refers to Law No.30 of 1999 concerning Arbitration and Alternative Dispute Resolution, while sharia arbitration is not set explicitly in the Law No. 30 of 1999 even in this act there is no article that offends the existence of sharia arbitration.The existence of sharia arbitration is recognized in the elucidation of Article 59 paragraph 1 of Law Number 48 of 2009 concerning the judicial power, which reads referred to arbitration under the provisions of the law including the sharia arbitration.There are some differences between national arbitration and sharia arbitration, the differences are the source of law, the legal principle , the jurisdiction of authority, pre-hearing phase, hearing phase and enforcement of the arbitral award phase.Keywords: National Arbitration, Sharia Arbitration , Comparative Study